MRNA Expression levels of genes involved in antitumor immunity: Identification of a 3-gene signature associated with prognosis of muscle-invasive bladder cancer. (2nd November 2017) - Le Goux, Constance; Vacher, Sophie; Pignot, Géraldine; Sibony, Mathilde; Barry Delongchamps, Nicolas; Terris, Benoit; Piaggio, Eliane; Zerbib, Marc; Damotte, Diane; Bieche, Ivan
ABSTRACT: Immunotherapy for bladder cancer has given promising results. Here we aimed to evaluate the possible involvement and prognostic value of 33 genes involved in the immune response during bladder carcinogenesis. Expression levels were assessed by quantitative real-time RT-PCR in normal and tumor human bladder samples. Immunohistochemistry was performed to evaluate the protein expression of 2 genes and relation of the mRNA and protein levels was analyzed. Tumors were obtained from 154 patients (83 with muscle-invasive bladder cancer [MIBC] and 71 non-MIBC [NMIBC]) who underwent transurethral bladder resection or radical cystectomy between 2002 and 2006. All patients signed an informed consent. Results of molecular analyses were coupled with survival analyses. Overall, 25 genes (75.8%) were significantly overexpressed in MIBC and 15 (45.5%) were deregulated in NMIBC as compared with normal tissue. On multivariate analysis, risk of NMIBC recurrence was increased with high FOXP3 / CD8 ratio and overexpression of OX40L (p = 0.016 and p = 0.0039, respectively). In MIBC, a molecular signature of 3 genes ( OX40L, CD8 and TIGIT ) was significantly associated with prognosis in terms of recurrence-free and overall survival (p = 0.0007 and p = 0.007). RT-PCR findings were confirmed by immunohistochemistry for CD8 and FOXP3, with high association between mRNA and protein levels. Finally, risk of recurrence of non–muscle-invasive bladder cancer was increased with high FOXP3 / CD8 ratio and OX40L overexpression. We identified a 3 gene molecular signature associated with prognosis of muscle-invasive bladder cancer. These results confirm the useful role of immune checkpoints in bladder carcinogenesis and suggest targets for therapy.